1994
DOI: 10.1207/s15327655jchn1101_6
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Diagnosis in Home Care: Audit Tool Development

Abstract: Little research has been done to document the value of using nursing diagnosis in home care and the impact that increased acuity levels have had in diagnostic selection. Nursing diagnosis documentation in home care was examined to see whether it had a relation to select client and visit pattern variables. This retrospective chart audit, which piloted a newly developed instrument called the Home Care Audit Tool, utilized a sample of 199 closed records of a large midwestern Visiting Nurse Association. The mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
4
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
5
4
0
Order By: Relevance
“…The mean age was 66.8 years; among the individuals, 55% were female and the highest prevalence was of circulatory system diseases. These data are corroborated by other international studies (6)(7)(8)(9) . Globally, demographic and epidemiological changes have taken place, and Brazil follows these trends, such as the increase in the number of elderly people and the phenomenon of feminization of aging, due to women's longer life expectancy (14)(15) .…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The mean age was 66.8 years; among the individuals, 55% were female and the highest prevalence was of circulatory system diseases. These data are corroborated by other international studies (6)(7)(8)(9) . Globally, demographic and epidemiological changes have taken place, and Brazil follows these trends, such as the increase in the number of elderly people and the phenomenon of feminization of aging, due to women's longer life expectancy (14)(15) .…”
Section: Discussionsupporting
confidence: 90%
“…In the Elimination and change domain, the diagnosis of impaired urinary elimination was identified, which was related to multiple causes and evidenced by the defining feature of urinary incontinence. Like other studies (6)(7)(8) , this diagnosis was commonly found in patients in HC. In these patients, changes in the genitourinary system are relevant (18) .…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations